Differential Exposure and Differential Vulnerability to Unhealthy Food Consumption in Relation to Dental Caries Among Brazilian Children and Adolescents - Rafael Aiello Bomfim; Luiza De Carli Grieleitow; Hazelelponi Naumann Cerqueira Leite; Amanda Barbosa Oliveira; Andreia Morales Cascaes; Paulo Frazão (International Journal of Environmental Research and Public Health, 2026)
Objectives: To assess differential exposure and differential vulnerability to frequency of unhealthy food consumption in relation to dental caries among 5-year-old children and 12-year-old adolescents in Brazil. Methods: This cross-sectional study included 836 participants, comprising 445 children and 391 adolescents from municipalities in Mato Grosso do Sul, Brazil. Dental caries experience was assessed using the decayed, missing and filled surfaces index for primary teeth among children (dmfs) and permanent teeth among adolescents (DMFS). Unhealthy food consumption was measured according to the weekly frequency of sugar-sweetened beverages and ultra-processed foods and categorized as low, moderate or high. Socioeconomic position was assessed using equivalized per capita household income and parental schooling. Differential exposure was examined by assessing socioeconomic gradients in unhealthy food consumption. Differential vulnerability was assessed using interaction terms between socioeconomic position and unhealthy food consumption in negative binomial regression models. Absolute and relative inequalities were quantified using the Slope Index of Inequality and Relative Index of Inequality. Results: Adolescents from lower-income and lower-education households showed a higher frequency of unhealthy food consumption, whereas this pattern was not clearly observed among children. Socioeconomic inequalities in dental caries were evident in both age groups. However, evidence that socioeconomic position modified the association between frequency of unhealthy food consumption and caries was stronger and more consistent among adolescents. Sensitivity analyses using caries prevalence as a binary outcome supported this pattern. Inequality measures indicated stronger relative socioeconomic gradients among adolescents than among children. Conclusions: Socioeconomic inequalities in dental caries are shaped by unequal exposure to unhealthy food consumption and unequal vulnerability to its effects, particularly during adolescence.